2023
DOI: 10.1038/s41467-023-36786-5
|View full text |Cite
|
Sign up to set email alerts
|

Diamagnetic mechanism of critical current non-reciprocity in multilayered superconductors

Abstract: The suggestion that non-reciprocal critical current (NRC) may be an intrinsic property of non-centrosymmetric superconductors has generated renewed theoretical and experimental interest motivated by an analogy with the non-reciprocal resistivity due to the magnetochiral effect in uniform materials with broken spatial and time-reversal symmetry. Theoretically it has been understood that terms linear in the Cooper pair momentum do not contribute to NRC, although the role of higher-order terms remains unclear. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…As for the mechanism of the SDE, while the intrinsic mechanism based on the asymmetry of the band structure has been proposed, [16][17][18] several extrinsic mechanisms have also been reported. [5,[13][14][15] In this study, we demonstrated a zero-field SDE with an efficiency of up to 40% in Fe-inserted non-centrosymmetric Nb/V/Ta superconducting artificial superlattices. The polarity and magnitude of the zero-field SDE were controlled by the direction of magnetization, suggesting the existence of an effective exchange field on the Cooper pairs.…”
Section: Introductionmentioning
confidence: 59%
See 2 more Smart Citations
“…As for the mechanism of the SDE, while the intrinsic mechanism based on the asymmetry of the band structure has been proposed, [16][17][18] several extrinsic mechanisms have also been reported. [5,[13][14][15] In this study, we demonstrated a zero-field SDE with an efficiency of up to 40% in Fe-inserted non-centrosymmetric Nb/V/Ta superconducting artificial superlattices. The polarity and magnitude of the zero-field SDE were controlled by the direction of magnetization, suggesting the existence of an effective exchange field on the Cooper pairs.…”
Section: Introductionmentioning
confidence: 59%
“…To gain further insight into the observed SDE, we investigated possible extrinsic contributions, such as asymmetric edges, [14] Meisner screening currents originating from magnetization, [14] and Josephson vortices. [15] When superconductivity breaks from the edge of the sample, the sign of Q should change depending on which end of the sample the superconductivity starts to break from. First, we verified the contribution of asymmetric edges [14] by examining the reproducibility of Q.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Type II superconductors (type II SCs) are distinguished by their characteristic mixed state in the phase diagram due to the appearance of superconducting vortices [1]. The dynamics of these Abrikosov vortices can be modified by applied current, external magnetic field, sample geometry/confinement [2,3], and magnetic proximity effect [4][5][6], thereby opening various possibilities for controlling device properties, for instance, the superconducting diode effect (SDE) [7][8][9]. The appearance of nonreciprocal current-voltage characteristics in a superconductor has received revived interest following the observation of field-free superconducting rectification effects in van der Waals heterostructures (vdWHs) and multilayered Rashba superconductors [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In the meantime, it has been realized that higher superconducting diode efficiency can be achieved in properly designed nanostructures in which the time-reversal symmetry is broken via trapped fluxes or an external magnetic field. However, a magnetic field is often undesired for integrating the devices in superconducting circuits. In this work, we rectify this problem by creating superconducting diodes which can operate at zero external magnetic field and achieve efficiency approaching 100%.…”
mentioning
confidence: 99%